2007
DOI: 10.1029/2006jb004615
|View full text |Cite
|
Sign up to set email alerts
|

Strong ground motion simulation of the 1999 Chi‐Chi, Taiwan earthquake from a realistic three‐dimensional source and crustal structure

Abstract: [1] We simulate the strong ground motion of 1999 Chi-Chi, Taiwan earthquake (M w = 7.6) by considering a three-dimensional source rupture model in a full waveform three-dimensional wave propagation study. The strong ground motion records during the 1999 Chi-Chi earthquake show various characteristics at different sites in Taiwan. We adopt a three-dimensional source model derived from an inversion study with identical path effects as considered in this three-dimensional forward study. Comparisons between the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…Some features of the Chi-Chi earthquake from the ground acceleration field, ground velocity field, and ground displacement field data, based on [5] and [6] are listed below: (1) The peak ground acceleration (PGA) is generally higher in the northern part of the source region. (2) The shaking motion occurs along the northward rupture direction.…”
Section: Resultsmentioning
confidence: 99%
“…Some features of the Chi-Chi earthquake from the ground acceleration field, ground velocity field, and ground displacement field data, based on [5] and [6] are listed below: (1) The peak ground acceleration (PGA) is generally higher in the northern part of the source region. (2) The shaking motion occurs along the northward rupture direction.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that more buildings are damaged on the hanging wall compared with the buildings on the footwall. The phenomena can be attributed to the hanging wall effect of strong ground motion (Abrahamson and Somerville 1996;Allen et al 1998;Lee et al 2007) and/or the complex surface deformation pattern on the hanging wall (Lee et al 2000). The earthquake-triggered landslides also show significant near fault and hanging wall effects (Sato et al 2007;Yagi et al 2009 Yin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively speaking, the influence of earthquakes on the slopes along the Ali Mountain Highway has been less severe compared to the heavy rainfall. A total of 24 landslides were triggered by the 1998 Jueili earthquake (977 m 3 ) and the 1999 Chi-Chi earthquake (23634 m 3 ) along the Ali Mountain Highway (Lee et al 2005). However, the strong motion induced by the earthquake had a lasting effect on the stability of the slopes for more than 5 years (Lee et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…By inverting the broadband seismic records, the source parameters (e.g., Kao and Jian 1999;Kao et al 2001) and the source rupture process (e.g., Lee et al 2008Lee et al , 2010Huang et al 2011) can be determined. In addition, broadband data also provides a constraint for wave propagation simulation on validating models (e.g., Lee et al 2007). The difference between calculated and observed data can be used to evaluate the seismic site effect.…”
Section: Broadband Seismographic Systemmentioning
confidence: 99%